2022
DOI: 10.1038/s41598-022-19115-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure parameter design and bench test research of paddy field blades

Abstract: Aiming at the problems of high labor intensity and low efficiency in manual operation during the pulping process of rice seedling nursing in thin mud in hilly and mountain areas, this paper designed a new type of paddy field blade for seedling nursing, and utilized a rice nursery pulper to help manual operation complete the pulping process. It created a mathematical model of mud-throwing mass and operating power in the operation process of paddy field blade, and obtained the main structure factors that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, it should be noted that mud spreader blades possess structural characteristics that differ from commonly used agricultural machinery blades; thus, their operational characteristics when interacting with mud exhibit distinctions from ordinary blades. Consequently, a series of studies on technical aspects and methods for utilizing paddy field machinery have been conducted by researchers [28][29][30][31][32][33][34][35][36][37]. Zhang, Y. et al [38] optimized the operational parameters of a weeder blade used in rice fields, and their results demonstrated that the optimized blade achieved satisfactory performance according to agronomic requirements.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that mud spreader blades possess structural characteristics that differ from commonly used agricultural machinery blades; thus, their operational characteristics when interacting with mud exhibit distinctions from ordinary blades. Consequently, a series of studies on technical aspects and methods for utilizing paddy field machinery have been conducted by researchers [28][29][30][31][32][33][34][35][36][37]. Zhang, Y. et al [38] optimized the operational parameters of a weeder blade used in rice fields, and their results demonstrated that the optimized blade achieved satisfactory performance according to agronomic requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the operational performance of blade cutters, Xie Y et al [32,33] optimized the structural parameters of the blades for use in paddy fields using a CFD method, and the results showed that the optimal blade performance was greatly improved. Chen C et al [34] optimized the design of blades in rice seedling growth trays for mud homogenization through discrete element simulations. Ding Q et al [35] utilized reverse engineering technology to determine the essential geometric parameters of the pulping blade, subsequently investigating both the operational aspects and design methodology of said blade.…”
Section: Introductionmentioning
confidence: 99%